Effects of storage structures and moisture contents on seed quality attributes of quality protein maize - Bhandari, Gopal; Ghimire, Tara Bahadur; Kaduwal, Sangita; Shrestha, Jiban; Acharya, Ramesh (Journal of Maize Research and Development, 2018)
The study was aimed to examine the effects of various storage structures and moisture contents on seed quality attributes of quality protein maize seed. The quality protein maize (QPM-1) seed was tested in conventional seed storage containers (Fertilizer sack and earthen pot) and the improved hermetic ones (Metal bin, Super grain bag, and Purdue Improved Crop Storage (PICS) bag) at Seed Science and Technology Division, Khumaltar, Nepal during February, 2015 to January 2016. Ten treatments comprising 5 storage devices in two moisture regimes (11% and 9%) replicated thrice and laid out in Completely Randomized Design (CRD). Data on temperature, relative humidity (RH), germination, electrical conductivity (EC), seed moisture content (MC) were collected bimonthly. The conventional containers were found liable to the external environmental condition whereas the hermetic structures observed with controlled RH level below 40% in all combinations. Electrical conductivity (EC) for seed vigor showed that hermetic containers provide higher seed vigor than the conventional ones. Up to 4 months all treatments were found statistically at par for germination. A significant difference was observed in each treatment after 4 months where PICS bag & Super grain bag showed best germination followed by metal bin while fertilizer bag & earthen-pot showed poorer and poorest germination respectively till one year. Almost all treatments with lower MC showed better results than the treatments with higher MC. A negative correlation (R2=69.7%) was found between EC and Germination. All six figures from 2 to 12 months on MC showed statistically different where hermetic plastic bags were found maintaining MC as initial whereas MC of fertilizer bags and earthen pot was spiked than the basal figure. The finding evidenced that the hermetic containers and low MC are the seed storage approaches for retaining the quality of seed even in an ambient environmental condition for more than a year.